2023
DOI: 10.1002/14651858.cd008721.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-vascular endothelial growth factor for proliferative diabetic retinopathy

Abstract: Anti-vascular endothelial growth factor for proliferative diabetic retinopathy (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 174 publications
0
1
0
Order By: Relevance
“…Further studies confirmed that anti-VEGF therapy is non-inferior to PRP for the treatment of PDR [ 57 ]. Recent studies have shown benefit from intravitreal anti-VEGF alone in the treatment of PDR [ 58 , 59 , 60 ], although visual recovery is slower [ 61 ], and patients who are lost to follow-up after anti-VEGF alone are at risk of worse visual outcomes than if they had received laser treatment [ 62 ]. The combination of anti-VEGF and PRP is widely used clinically, but the benefit over PRP alone is modest [ 60 ].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Further studies confirmed that anti-VEGF therapy is non-inferior to PRP for the treatment of PDR [ 57 ]. Recent studies have shown benefit from intravitreal anti-VEGF alone in the treatment of PDR [ 58 , 59 , 60 ], although visual recovery is slower [ 61 ], and patients who are lost to follow-up after anti-VEGF alone are at risk of worse visual outcomes than if they had received laser treatment [ 62 ]. The combination of anti-VEGF and PRP is widely used clinically, but the benefit over PRP alone is modest [ 60 ].…”
Section: Diabetic Retinopathymentioning
confidence: 99%